Seedling morphology of Ormosia smithii Rudd and its systematic relevance in Ormosia (Leguminosae, Papilionoideae) - Hartmann, Leonardo da Silva; Rodrigues, Rodrigo Schütz (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
This paper describes and illustrates the early development and seedling morphology of Ormosia smithii Rudd, providing a review on the systematic relevance of seedling traits to the Neotropical Ormosia infrageneric classification. Seeds of O. smithii were collected from wild populations in Roraima State, Brazil. The species possesses cryptocotylar, hypogeal seedlings with storage cotyledons, with stipulate and 1-foliolate eophylls at the first three nodes. As currently delimited, sections and series of Neotropical Ormosia show a variation in seedling morphology groups and first eophyll phyllotaxy. However, with a few possible exceptions, seedling traits do not provide diagnostic characters for these infrageneric taxa in Ormosia. Although seedlings traits were relatively uniform within O. sect. Ormosia ser. Coccinea, O. smithii can be separated from the other Amazonian species of this series on the basis of epicotyl length.
Keywords: Post-seminal development; Embryo; Fabaceae; Mimosoideae; Testa